Um percurso de estudo e pesquisa a distância em uma formação continuada de professores de matemática para o ensino de quadriláteros - García-Cuéllar, Daysi Julissa (2021)
This research aims to elaborate, implement and analyze a Study and Research Path in-service teacher education (SRP-TE), for distance teaching of quadrilaterals in Peru. The research is inserted in the theoretical framework of the Anthropological Theory of Didactics – ATD, which had as subjects secondary mathematics teachers in Peru, and used as qualitative methodology the Didactic Engineering in ATD. SRP is a didactic device that seeks the transition from the monumental paradigm of visiting works to the paradigm of questioning the world, which involves the study of issues, media, and milieu, etc., all this, in turn, implies the search for an answer to a generating question through other questions and answers. In this sense, the SRP-TE also starts from a generating question, based on contexts related to teacher education and a teaching object at the school level of teachers. The development of this training device is composed of five modules: M0: Starting from a professional question; M1: Experiencing a study and research path; M2: analyze the SRP experienced; M3: designing a SRP and M4: managing and experimenting an SRP. Research methodology is developed in four phases: in the first phase, which involves preliminary analyses, we carried out an epistemological study of quadrilaterals to build a Reference Epistemological Model – REM, and an economic and ecological study of quadrilaterals to identify the Dominant Model – DM in the Peruvian educational system. In the second phase, design and a priori analysis, the SRP-TE distance device for teaching quadrilaterals is planned and a priori analysis of what was planned is carried out; in the third phase, experimentation, or in vivo analysis the plan is implemented and analyzed during its execution, Finally, in the fourth phase, a posteriori analysis, the results are compared with the a priori analysis. As a result of the research, it is inferred that the distance SRP-TE contributed to the in-service teacher education because it led them to question and reflect on their practice and to realize the possibility of teaching quadrilaterals from the generating question How to prevent a tsunami? However, during the third module, they remained in the dominant model, presenting SRPs that only changed the context of the SRP experienced, but as a positive point they did not return to textbooks. Teachers stated that the greatest difficulty lies in preparing the generating question and that they needed to experience other SRPs to feel more confident secure in using them in the classroom, since students would be the protagonists and could present and answer their own questions